PERBANDINGAN POLA PERESEPAN ANTIHIPERTENSI DI SALAH SATU APOTEK KOTA DAN KABUPATEN SEMARANG - Fef Rukminingsih; Cenvi Chindiana; Amara Aolia Anggraini (Jurnal Farmasi IKIFA, 2024)
Hypertension is a blood vessel condition that has systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg. Antihypertensive prescribing patterns are used as a basis for maintaining drug stock availability. The two pharmacies being compared are both located in densely populated areas with high levels of stress. The aim of this study was to determine differences in antihypertensive prescribing patterns in pharmacies in Semarang City and Semarang Regency. The type of research carried out was descriptive observational research with a cross sectional study design using retrospective data obtained from antihypertensive prescription sheets at one of the pharmacies in Semarang City and Regency for the period October – December 2022. The data taken included; date of prescription writing, patient age, gender, type and amount of antihypertensive. The data obtained was then analyzed qualitatively and quantitatively. Qualitative analysis was carried out by grouping based on age, gender, type of antihypertensive, antihypertensive drug class, and single or combination use. Quantitative analysis is carried out by calculating the percentage. The number of prescription sheets obtained at one of the Semarang City pharmacies was 141 and at one of the Semarang Regency pharmacies was 118. The number of female patients in both pharmacies is greater than male patients. The age of patients in both pharmacies was mostly in the range of 46-55 years. The most antihypertensive prescriptions in one of the Semarang City pharmacies is amlodipine while in Semarang Regency it is candesartan. Most antihypertensive use in both pharmacies was single use. The prescribing patterns at the two pharmacies are different even though they are both located in densely populated areas.